Thinking of norms—or being told what they are: The effect of social information on donation decisions - Hagit Sabato (PLoS ONE, 2025)
The effect of social information (descriptive versus injunctive norms) on people’s donation decisions was examined in two studies. In Study 1 (N=376) participants received information about the norm (a high versus a low anchor) for each norm type, while in Study 2 (N=392) participants were instructed to think of the social norm (what one ought to do vs. what most people do) before their donation decision. Results suggest that when actual information was given (Study 1), a high anchor reduced participants’ initial willingness to donate—but among those who did decide to donate, the high anchor resulted in greater donation amounts than the low anchor. This pattern held true for both injunctive and descriptive norms. Merely thinking about the injunctive norm—without any anchor (Study 2)—increased donations, compared with thinking about the descriptive norm, or control conditions. Possible explanations, and the implications for charitable giving are discussed.